Plasma N-acetyl-glucosaminidase in advanced gastro-intestinal adenocarcinoma correlates with age, stage and outcome. (January 2015) - Hartmann, Daniel; von Figura, Guido; Song, Zhangfa; Harden, Sharon; Scott, Lucy C; Evans, TR Jeffry; Rudolph, Karl Lenhard; Bilsland, Alan E; Keith, W Nicol
ABSTRACT : Background:   N -acetyl-glucosaminidase (NAG) is a potential marker of genotoxicity. We retrospectively analyzed plasma NAG and clinico-pathologic features in advanced gastrointestinal adenocarcinoma patients.Methods: Plasma from 118 patients and 51 healthy volunteers was analyzed for associations between NAG levels and age, disease presence, stage, treatment responses and survival.Results: Pretreatment NAG correlated with age but was independently increased in metastatic versus locally advanced disease, particularly in gastric/esophageal patients. NAG was also associated with reduced overall survival. In subgroup analysis, increased NAG activity between day 1 and 2 of chemotherapy cycle 1 correlated with treatment response.Conclusion: We demonstrated that NAG correlates with gastrointestinal cancer outcomes. Further studies are required to determine if plasma markers of genotoxicity can be useful for disease monitoring.